Methods of construction of three-dimensional models of details - Dereza, Olena; Дереза, Олена Олександрівна; Дереза, Елена Александровна; Movchan, Serhii; Мовчан, Сергій Іванович; Мовчан, Сергей Иванович; Boltianskyi, Borys; Болтянський, Борис Володимирович; Болтянский, Борис Владимирович; Dereza, Serhii; Дереза, Сергій Володимирович; Дереза, Сергей Владимирович (ТДАТУ, 2020)
EN: This article discusses the main types and programs for 3D modeling. A review and analysis of literature sources related to the subject of three-dimensional modeling, on the basis of which the peculiarities of the formation of the construction of modern 3D forms were revealed. The main software products are presented, with the help of which it is easy to create 3D objects, mainly for technical products and design. The spheres of application of this technology, the basic programs and types of 3D modeling are defined. The following bases of technique of creation of three-dimensional models are allocated in the work: solid-state modeling, polygonal modeling, procedural modeling, digital sculpture (sculpting), modeling by means of splines. The basic principles of 3D modeling determine the selection of modeling methods in different design situations. In systems of automated design and preparation of technical documentation solid-state modeling is most used. But the main stages of product creation are the same regardless of the method of modeling. An example of the algorithm of modeling stages for obtaining the finished product is given. Creating solid models is more important than ever today. It is important not only to create an object quickly, but also to edit it just as quickly. Solid state modeling has these qualities, so it is considered the most advanced technology. 3D modeling and design not only create virtual objects and 3D images, but also make them a reality. This leads to the widespread use of computer graphics technology and their application in all areas of human activity. Therefore, providing a detailed description of modeling techniques using various techniques for creating 3D objects is relevant. RU: В данной статье рассмотрены основные виды и программы для 3D моделирования. Проведен обзор и анализ литературных источников, касающихся тематики трехмерного моделирования, на основе которых было обнаружено особенности формообразования построения современных 3D форм. Основные принципы 3D моделирование обусловливают подбор способов моделирования в различных проектных ситуациях. В системах автоматизированного проектирования и подготовки технической документации наиболее применяется твердотельное моделирование. Но основные этапы создания продукта одинаковы независимо от способа моделирования. Приведен пример алгоритма этапов моделирования на получение готового продукта. Создание твердотельных моделей как никогда сегодня актуально. Важно не только быстро создавать объект, но и так же быстро редактировать его. Твердотельное моделирование обладает данными качествами, поэтому оно считается самой совершенной технологии. Поэтому предоставление детального описания методик моделирования с использованием различных техник создания 3D объектов является актуальным. UK: В даній статті розглянуто основні види та програми для 3D моделювання. Проведено огляд та аналіз літературних джерел, що стосуються тематики тривимірного моделювання, на основі яких було виявлено особливості формоутворення побудови сучасних 3D форм. Представлено основні програмні продукти, за допомогою яких легко створити 3D об’єкти, переважно для технічних виробів та дизайнерського проектування. Визначено сфери застосування даної технології, основні програми та види 3D моделювання. В роботі виділено такі основі техніки створення тривимірних моделей: твердотільне моделювання, полігональне моделювання, процедурне моделювання, цифрова скульптура (скульпуринг), моделювання за допомогою сплайнів. Основні принципи 3D моделювання обумовлюють підбір способів моделювання в різних проектних ситуаціях. В системах автоматизованого проектування та підготовки технічної документації найбільш застосовується твердотільне моделювання. Але основні етапи створення продукту однакові незалежно від способу моделювання. Наведено приклад алгоритму етапів моделювання щодо отримання готового продукту. Створення твердотільних моделей як ніколи сьогодні актуально. Важливо не тільки швидко створювати об'єкт, але і так само швидко редагувати його. Твердотільне моделювання володіє даними якостями, тому воно вважається найдосконалішою технологією. За допомогою 3D моделювання та проектування не тільки створюють віртуальні об’єкти та 3D зображення, але й втілюють їх у реальність. Це зумовлює велику поширеність комп’ютерних графічних технологій та їх застосування в усіх галузях людської діяльності. Тому надання детального опису методик моделювання із використанням різних технік створення 3D об’єктів є актуальним.
Способы построения трехмерных моделей деталей
Способи побудови тривимірних моделей деталей
Keywords: 3D modeling; modeling method; SolidWorks; AutoCAD; construction algorithm; model of detail; software; solid modeling; способ моделирования; 3D моделирование; алгоритм построения; модель детали; программное обеспечение; твердотельное моделирование; 3D моделювання; спосіб моделювання; алгоритм побудови; модель деталі; програмне забезпечення; твердотільне моделювання